PHF13: A new player involved in RNA polymerase II transcriptional regulation and co-transcriptional splicing. Issue 2 (15th March 2017) - Fuchs, Alisa; Torroba, Marcos; Kinkley, Sarah
ABSTRACT: We recently identified PHF13 as an H3K4me2/3 chromatin reader and transcriptional co-regulator. We found that PHF13 interacts with RNAPIIS5P and PRC2 stabilizing their association with active and bivalent promoters. Furthermore, mass spectrometry analysis identified ∼50 spliceosomal proteins in PHF13s interactome. Here, we will discuss the potential role of PHF13 in RNAPII pausing and co-transcriptional splicing.